2016
DOI: 10.1242/bio.016246
|View full text |Cite
|
Sign up to set email alerts
|

Trim37-deficient mice recapitulate several features of the multi-organ disorder Mulibrey nanism

Abstract: Mulibrey nanism (MUL) is a rare autosomal recessive multi-organ disorder characterized by severe prenatal-onset growth failure, infertility, cardiopathy, risk for tumors, fatty liver, and type 2 diabetes. MUL is caused by loss-of-function mutations in TRIM37, which encodes an E3 ubiquitin ligase belonging to the tripartite motif (TRIM) protein family and having both peroxisomal and nuclear localization. We describe a congenic Trim37 knock-out mouse (Trim37−/−) model for MUL. Trim37−/− mice were viable and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
(81 reference statements)
1
17
0
Order By: Relevance
“…Interestingly, peroxisomes appear to be normal in TRIM37 knockout mice ( Kettunen et al, 2016 ). To resolve this apparent discrepancy, we silenced TRIM37 in a mouse cell line, Raw264.7.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, peroxisomes appear to be normal in TRIM37 knockout mice ( Kettunen et al, 2016 ). To resolve this apparent discrepancy, we silenced TRIM37 in a mouse cell line, Raw264.7.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that the TRIM family was involved in innate immune response ( 14 ), none of the published evidence associated T lymphocyte derangement with TRIM37 mutations in MUL syndrome ( 5 , 10 ). It is likely that the specific TRIM37 mutations present in our MUL case ( 4 ) encoded for a defective TRIM37 protein, altering its conformation, cellular localization, and protein-protein interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Haraldsson et al revealed humoral immunodeficiency in a patient affected by MUL syndrome (9). However, none of the published evidence reported adaptive immune response defects in MUL individuals (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, further studies are needed to confirm the dynamics of H2A ubiquitination in primary cells from individuals with MUL. The spectrum of phenotypes described for the Trim37 −/− mouse model recapitulates many clinical features of MUL and thus provides a good model to study pathogenesis related to TRIM37 deficiency [52]. Despite the prominent neurological features of MUL, the role of TRIM37 in neural development has not been investigated.…”
Section: Histone H2a Ubiquitination Syndromesmentioning
confidence: 99%